A generalization of an integral arising in the theory of distance correlation - Dueck, Johannes; Edelmann, Dominic; Richards, Donald (Statistics & probability letters, 2015)
We generalize an integral which arises in several areas in probability and statistics and which is at the core of the field of distance correlation, a concept developed by Székely et al. (2007) to measure dependence between random variables.